2015
DOI: 10.1007/s11277-015-2689-3
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic Sub-channel and Transmit Power Allocation in an OFDMA Based Cognitive Femtocell Network

Abstract: The paper proposes a scheme to minimize the co-tier and cross-tier interference by properly allocating the sub-channels and power among the femtocell users (FUs) in an OFDMA based cognitive femtocell network. An efficient graph coloring based sub-channel allocation scheme is adapted in which the sub-channels in the uplink band of the macrocell are shared by the femtocells dynamically in an opportunistic way through spectrum sensing. A price-based power allocation scheme using game theory is proposed to assign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Several dynamic ICIC techniques are introduced [11][12][13]; some of them adjust frequency and power allocation in each cell locally, without any cooperation between eNodeBs. Other techniques depend on the signaling exchange between neighboring eNodeBs.…”
Section: Icic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several dynamic ICIC techniques are introduced [11][12][13]; some of them adjust frequency and power allocation in each cell locally, without any cooperation between eNodeBs. Other techniques depend on the signaling exchange between neighboring eNodeBs.…”
Section: Icic Approachesmentioning
confidence: 99%
“…Several dynamic ICIC techniques are introduced [11][12][13]; some of them adjust frequency and power allocation in each cell locally, without any cooperation between eNodeBs. For instance, the heuristic power control algorithm introduced in [14] is an autonomous dynamic ICIC technique.…”
Section: Icic Approachesmentioning
confidence: 99%
“…In [10], the authors have suggested an interference avoidance strategy for two-tier femtocell network in code division multiple access (CDMA)-based system. Many other techniques have been proposed in the literature in order to manage the interference issues in femtocell networks such as using power control [11,12], resource allocation [13,14], using multiple antennas [15][16][17][18] and so on. Along with interference mitigation by power control our work mainly deals with the cooperation of femtocells with macrocell to increase the data rate of indoor macrocell users (MUs).…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism works jointly along with the pricing‐based power control scheme. The pricing‐based power control part is partially adapted from our previous work [13]. However, the incentive‐based femtocell cooperation jointly with power control is entirely a new approach. The rest of this paper is organised as follows.…”
Section: Introductionmentioning
confidence: 99%